Reviews - Darcy Meeker; James W. King (Journal of Applied Communications, 1988)
Reviews of "Discovering the Future; The Business of Paradigms," by Joel Baker; Translate to Communicate: A Guide for Translators, by Mary M.F. Massoud; A Farmer's Primer on Growing Soybeans on Riceland, by R. K. Pandey.